Validation of the CFD-DPM solver DPMFoam in OpenFOAM (R) through analytical, numerical and experimental comparisons - Fernandes, Célio Bruno Pinto (2018)
Multiphase flows are relevant in several industrial processes mainly because they are present in the production of a large diversity of products. Hence, the availability of accurate numerical modeling tools, able to cope with this type of flows, is of major significance to provide detailed information about the system characteristics, in order to guide the design activity. This study presents a detailed assessment of a multiphase flow solver able to couple Eulerian and Lagrangian phases, the last modeled through the discrete particle method. The numerical code is already implemented in the open source computational fluid dynamics software package OpenFOAM ®. The solver (DPMFoam) is firstly used to simulate the collision between two particles, for which a good correlation was obtained with the theoretical impulse force value. Subsequently, the solver is employed in the simulation of a pseudo 2D gas-solid flow in a fluidized bed. In this case study, the results obtained for the bubble patterns, time-average flow patterns, bed expansion dynamics and particle phase energy analysis are in agreement with the experimental and numerical results available in the literature. In addition, the numerical pressure drop for the fluidized bed is computed and compared with the analytical Ergun’s pressure drop equation. The accuracy of the numerical results was found to be sensitive to the solid fraction estimation.